Legal and Institutional Aspects of the Financial Sector in Handling the COVID-19 Pandemic - Yunus Husein; Ichsan Zikry (Bank Indonesia, 2022)
The Covid-19 pandemic has negatively impacted economic conditions, health, and social activities of the community. This study elaborated on two things. First, the legal aspects of handling the Covid-19 Pandemic. Second, it outlines the aspects of institutions involved in handling the Covid-19 Pandemic. The results of this study show that the legal aspects of the Government in dealing with the Covid-19 Pandemic are through Law No. 2 of 2020. In this regulation, at least two main things are regulated, namely the legal protection of members of the Financial System Stability Committee (KSSK) from lawsuits in exercising their authority and exceeding the deficit limit of 3 percent of GDP, furthermore, regarding institutions involved in handling the Covid-19 Pandemic, it is necessary to strengthen institutions. In this case, the institution in question is included in the KSSK members, because of its large authority in handling the Pandemic, especially for national economic recovery, as well as large state budget allocations. The strengthening efforts that can be done are First, amendments to Law No. 2 of 2020, especially regarding the protection of the KSSK against claims and exemptions from state financial losses. Second, the issuance of a PERPPU on supervision and reporting of financial responsibility for handling the Covid-19 Pandemic. Through these institutional strengthening efforts, it is hoped that the handling of the Pandemic, especially in the context of national economic recovery, can run optimally.